2011
DOI: 10.2308/jiar-10081
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of Corporate Risk Disclosure: An International Investigation in the Manufacturing Sector

Abstract: This paper is the first multi-country investigation of comprehensive corporate risk disclosure. Based on a detailed content analysis of 160 annual reports, we analyze the attributes and the quantity of risk disclosure and its association with the level of firm risk in the U.S., Canadian, U.K., and German settings. We find a consistent pattern where risk disclosure is most prevalent in management reports, concentrates on financial risk categories, and comprises little quantitative and forward-looking disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
238
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 192 publications
(272 citation statements)
references
References 35 publications
27
238
3
4
Order By: Relevance
“…The quality of risk disclosure is measured using the same list of items that is used for the volume and the crisis affected the way these items are disclosed and proved that the same categories of risk information are disclosed with more specific details. With regards to the determinants of the ERM disclosure, the results of the regression analysis show a positive and significant relation between SIZE and ERM disclosure (p = 0.000) for all the proxies of ERM disclosure which is consistent with our H2 and previous research (Beretta & Bozzolan, 2004;Dobler et al, 2011;Abraham & Cox, 2007). Results concerning DEBT are inconclusive.…”
Section: Multivariate Analysis For the Effect Of The Crisis On Erm DIsupporting
confidence: 59%
See 3 more Smart Citations
“…The quality of risk disclosure is measured using the same list of items that is used for the volume and the crisis affected the way these items are disclosed and proved that the same categories of risk information are disclosed with more specific details. With regards to the determinants of the ERM disclosure, the results of the regression analysis show a positive and significant relation between SIZE and ERM disclosure (p = 0.000) for all the proxies of ERM disclosure which is consistent with our H2 and previous research (Beretta & Bozzolan, 2004;Dobler et al, 2011;Abraham & Cox, 2007). Results concerning DEBT are inconclusive.…”
Section: Multivariate Analysis For the Effect Of The Crisis On Erm DIsupporting
confidence: 59%
“…Some researchers found that ERM disclosure is significantly associated with company size Abraham & Cox, 2007). Dobler et al (2011) found that risk disclosure is positively associated with the risk measures of American and Canadian companies, and negatively associated with the risk measures of German companies while found no relation between risk disclosure and measures of firm risk levels.…”
Section: Review Of Previous Research and Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in the US, Financial Reporting Release NO.48 (FRR 48) was introduced in 1997, and requires Securities Exchange regulator registrants to provide information in the management, discussion, and analysis section of the 10K-reports, which mainly focus on the materiality of risks and significant risk exposures, such as financial risk information relating to operations, financial condition, and forward-looking information. Similarly, Canada, North America, and Europe also require firms to disclose risk information in the management, discussion, and analysis section, including a description of business operations and description of risks and uncertainties (Dobler, Lajili, and Zéghal, 2011). …”
Section: Risk Management Disclosure In Different Settingsmentioning
confidence: 99%